Evaluating SDG 11 Coverage on Cimahi Urban Development Program - Indradjati, Petrus Natalivan; Hasan, Tika (European Publisher, 2019)
Before a Medium-Term Development Plan is in legal form, it must go through a Strategic Environmental Study (SES) to ensure every policy, plan, and programs have met the principles of sustainable development in Indonesians’ cities. The Medium-Term Development Plan is an urban development document containing non-spatial and spatial development programs, in this case, Cimahi for five years period. The process of formulating and legalise the Medium-Term Development Plan of Cimahi must be going through stakeholder and community participation as well as political arrangements with regional legislative councils. The latter process especially distorts the development programs from achieving the Sustainable Development Goal (SDG) 11 indicators and become the roots of urban problems. This paper explores (1) to what extent does the Cimahi’s urban development program still meets the SDG 11 indicators, and (2) to what extent does the participation and political processes influence changes in development programs. Evaluation result based on SDG 11 criteria and indicators on Cimahi’s urban development program through content analysis shows that there is distortion from the SDG 11 value mainly driven from more private interests and less of public interests.